EVALUASI KONSEP GREEN OPEN SPACE TERHADAP KUALITAS TAMAN PADA PROGRAM PENGEMBANGAN KOTA HIJAU (P2KH) KECAMATAN KENDAL (STUDI KASUS: TAMAN STADION UTAMA, LANGENHARJO, GAJAH MADA) - Majdina Astri Graharistiara; Hasti Widyasamratri (Universitas Islam Sultan Agung Semarang, 2017)
Green Open Space is an urban expanse covered by some of the trees as a shade area of the city and as the fulfillment of the needs public spaces for the community in activities and social. Efforts continue to be undertaken by the Green Open Space embodiment of Government, one that is by pioneering the implementation of ‘Program Pengembangan Kota Hijau’(P2KH) in improving the quantity and quality of Green Open Space in the area of the county or city. One form of Green Open Space i.e. the garden city that serves to improve the quality of urban and support the needs of the community in getting space to relax and leisure. The condition of children in district Kendal based on information from the community a lot of damage to either the environment or the facilities therein. This study aims to evaluate the application of Green Open Space on quality Grounds in the ‘Program Pengembangan Kota Hijau’(P2KH) sub district of Kendal which consists of the Stadion Utama, Langenharjo and Gajah Mada Parks. The method used was qualitative with deductive approach to rationalistic Unitarians. The analysis used a descriptive analysis i.e. qualitative and verification. Results from the study found that: 1) implementation evaluation results of Green Open Space in the gardens of the town Kendal not optimal, particularly on the Stadion Utama and Langenharjo Parks is still passive because it has not been supported with supporting facilities ; 2) evaluation results applying the Green Community is not optimal because there hasn't been an active ongoing activities so that it can not realize the active role of the community as a community in realizing the green city in district of Kendal; 3) factors that influence the application of optimal yet Green Open Space that is the location of the parks are not on the main road, the spread of vegetation are not optimal in improving microclimate because the settings are less noticed aspects of the function and benefits, passive Parks conditions due to lack of support facilities and the lack of appeal on the parks because the Setup and the pattern of plants that don't meet aesthetic; 4) factors that influence has not been optimal application of the Green Community that is constrained funds and lack of public awareness in maintaining and safeguarding the environment.